SAHABAT PASIEN DALAM ME-REINTERPRETASI SAKIT DI RUMAH SAKIT AL-IRSYAD SURABAYA - Nurhidayati, Nurhidayati; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2018)
Sahabat Pasien (the spiritual guidance for the patient) in Al-Irsyad Hospital, Surabaya has been existing for five years since 2013. Al-Irsyad Hospital is an Islamic hospital that involved ?Sahabat Pasien? who can provide spiritual needs even when needed to strengthen the mind of the patient in the healing process. The construction process carried out by a Sahabat Pasien is not only for the patient but also for all components of the hospital especially the employees to create as Islamic hospital culture. The theoretical framework of this research uses the social constructs of Peter L Berger and Thomas Luckman which is in the process through three stages namely externalization, objectivation, and internalization. This type of this research is qualitative research and how to determine of informants in this research is using a purposive technique. Data retrieval is using observation, interviews, documentation, and learning of literature. While the validity test of the data in this research used by data triangulation. The findings of this research carried out by sahabah pasien about some patient opinions of illness indicate that the illnesses are trials and tests from God, the forgiveness of sins and mistakes, degree appointment and others. Therefore, the patient could reinterpret the meaning of the pain by themselves, where they do confirmation of themselves that they are the part of the God?s creature and the last is how it could be the policy on their acting or making decisions. Keyword: spiritual needs, Islamic hospital culture, re-interpretation, illness, patient.